DEVELOPMENT OF EMOTIONAL INTELLECT IN ADOLESCENCE AND ITS ROLE IN CAREER CHOICE (International journal of artificial intelligence, 2025)
This article highlights the processes of developing emotional intelligence in adolescence and its role in career choices. According to the results of a study conducted among 9th and 11th-grade students, a comparative analysis of the indicators of emotional intelligence and professional orientations characteristic of age groups was conducted.